2017
DOI: 10.1155/2017/6073167
|View full text |Cite
|
Sign up to set email alerts
|

Do miRNAs Play a Role in Fetal Growth Restriction? A Fresh Look to a Busy Corner

Abstract: Placenta is the crucial organ for embryo and fetus development and plays a critical role in the development of fetal growth restriction (FGR). There are increasing evidences on the role of microRNAs (miRNAs) in a variety of pregnancy-related complications such as preeclampsia and FGR. More than 1880 miRNAs have been reported in humans and most of them are expressed in placenta. In this paper, we aimed to review the current evidence about the topic. According to retrieved data, controversial results about place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 73 publications
1
73
0
Order By: Relevance
“…133 Otherwise, studies have shown upregulation of miR-516-5p, miR-520a, miR520-h, miR-449a-5p, miR-92b, miR-191, and miR-204 in PE placenta samples. 133,134 These dysregulations of miRNAs may affect the development of PE.…”
Section: Mir-26amentioning
confidence: 95%
See 2 more Smart Citations
“…133 Otherwise, studies have shown upregulation of miR-516-5p, miR-520a, miR520-h, miR-449a-5p, miR-92b, miR-191, and miR-204 in PE placenta samples. 133,134 These dysregulations of miRNAs may affect the development of PE.…”
Section: Mir-26amentioning
confidence: 95%
“…With progression of disease, this miRNA expression was elevated, suggesting that the dysregulation of miRNA‐376c and 25‐OH‐VD mRNA was remarkably associated with urine protein and blood pressure in pregnant women and demonstrated that 25‐OH‐VD and miRNA‐376c interact with each other and involved in progression and occurrence of hypertensive disorder complicating pregnancy such as PE. By examining the placenta samples, there have been proven expressions of some miRNAs such as miR‐149, miR‐194, miR‐260‐5p, miR‐103a‐3p, miR‐145‐5p, miR‐16‐5p, miR‐100‐5p, and miR‐221‐3p downregulated in PE . Otherwise, studies have shown upregulation of miR‐516‐5p, miR‐520a, miR520‐h, miR‐449a‐5p, miR‐92b, miR‐191, and miR‐204 in PE placenta samples …”
Section: Epigenetic Changes In Pementioning
confidence: 99%
See 1 more Smart Citation
“…; Chiofalo et al . ). One potential approach is silencing the overexpressed miRs in these pathological conditions to decrease their unfavourable effects.…”
Section: Discussionmentioning
confidence: 97%
“…As the percentage of mosaicism does not correlate with the severity of congenital anomalies in PKS fetuses (Libotte et al ) other markers of severity and poor outcomes would be helpful. Recently, abnormal extracellular microRNAs (miRNAs) in maternal plasma have been showed early in Down syndrome pregnancies and in those pregnancies complicated by gestational diabetes, preeclampsia, fetal growth restriction (Chiofalo et al ; Kamhieh‐Milz et al ; Lagana’ et al ; Sebastiani et al ). As five miRNAs located on 12p have already been reported to be overexpressed in skin fibroblasts from PKS patients, further studies on maternal plasma miRNAs profile in PKS pregnancies might open a window to identify new potential diagnostic and prognostic biomarkers (Izumi et al ).…”
Section: Approach To Genetic Counseling and Conclusionmentioning
confidence: 99%